Flexible Solid-State Supercapacitor Based on a Metal–Organic Framework Interwoven by Electrochemically-Deposited PANI - Wang, Lu; Feng, Xiao; Ren, Lantian; Piao, Qiuhan; Zhong, Jieqiang; Wang, Yuanbo; Li, Haiwei; Chen, Yifa; Wang, Bo (Journal of the American Chemical Society, 2015)
Metal–organic frameworks (MOFs) have received increasing attention as promising electrode materials in supercapacitors (SCs). Yet poor conductivity in most MOFs largely thwarts their capacitance and/or rate performance. In this work, an effective strategy was developed to reduce the bulk electric resistance of MOFs by interweaving MOF crystals with polyaniline (PANI) chains that are electrochemically deposited on MOFs. Specifically we synthesized cobalt-based MOF crystals (ZIF-67) onto carbon cloth (CC) and further electrically deposited PANI to give a flexible conductive porous electrode (noted as PANI-ZIF-67-CC) without altering the underlying structure of the MOF. Electrochemical studies showed that the PANI-ZIF-67-CC exhibits an extraordinary areal capacitance of 2146 mF cm–2 at 10 mV s–1. A symmetric flexible solid-state supercapacitor was also assembled and tested. This strategy may shed light on designing new MOF-based supercapacitors and other electrochemical devices.